Evaluating the Knowledge, Attitude, and Perception of Medical Interns regarding Contraception in a Tertiary Care Centre - Usha NS; Sabari Anandh J V; Afzal Khan A K; Swapna R Nayaka (Universitas Padjadjaran, Indonesia, 2023)
Maternal mortality is one of the significant burdens requiring appropriate measures including family planning methods to control post-partum morbidity and mortality. The early age of marriage among women is accompanied by early pregnancies also contributes to maternal mortality. Knowledge about contraceptive usage could prevent such incidences. This study aimed to evaluate the knowledge, attitude, and perception regarding contraceptives among medical interns in our college. This cross-sectional questionnaire study was done on 60 house surgeons (interns), at MVJ Medical College and Research Hospital, Hoskote, using a validated questionnaire that consisted of 22 questions including MCQs and case scenarios to assess their knowledge, perception, and attitude about contraceptive methods. Data were analyzed in the form of percentages. Among 60 interns, 36 were females and the majority of students were from urban backgrounds. About 73.3% of interns had adequate knowledge about various contraceptive methods and their usage. The interns have a perception that illiteracy, lack of awareness and social, and religious values are major hurdles for contraceptive usage and have an attitude that doctors are most suitable to give information regarding contraceptive methods. Considering medical interns as future physicians and their responsible role in counseling about contraceptive usage in effective family planning, they need to have a positive attitude with fair knowledge and perception about the contraceptive methods which can be achieved by educating them early in their academic carrier.